2008
DOI: 10.1128/iai.00640-08
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Malaria Infection Triggers Early Expansion of Natural Killer Cells

Abstract: In order to gain a better understanding of gene expression during early malaria infection, we conducted microarray analysis of early blood responses in mice infected with erythrocytic-stage Plasmodium chabaudi. Immediately following infection, we observed coordinated and sequential waves of immune responses, with interferon-associated gene transcripts dominating by 16 h postinfection, followed by strong increases in natural killer (NK) cell-associated and major histocompatibility complex class I-related transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 55 publications
5
20
1
Order By: Relevance
“…1B), but then slowly (by day 168) returned to baseline levels. This decrease contrasts data from an animal model demonstrating that NK cells in the blood expand robustly and early after infection (40). Support for the notion that NK cells contribute to the anti-parasite immune response comes from a recent study that provided evidence that human NK cells bind to and eliminate infected red blood cells using cell contact-dependent mechanisms (53).…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…1B), but then slowly (by day 168) returned to baseline levels. This decrease contrasts data from an animal model demonstrating that NK cells in the blood expand robustly and early after infection (40). Support for the notion that NK cells contribute to the anti-parasite immune response comes from a recent study that provided evidence that human NK cells bind to and eliminate infected red blood cells using cell contact-dependent mechanisms (53).…”
Section: Discussioncontrasting
confidence: 97%
“…Thus, the initial inflammatory environment elicited by the infection may be sufficient to activate these cell populations leading to secretion of effector molecules such as IFNγ and TNFα. Importantly, animal model data suggest that the early inflammatory environment and particularly IFNγ seem to play an important role in the ensuing parasite control as well as disease progression, including development of cerebral malaria (10, 40, 41). It is currently unknown how accurately the mouse model mimics these innate-like lymphocyte responses in human infection since - to our knowledge - the function and fate of NK and innate-like T cells following Plasmodium infection of humans have not been elucidated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the findings of Mohan et al, other studies indicate similar P. chabaudi parasitemia in depleted mice and intact controls after NK1.1 MAb depletion of NK cells (19,41,53). Using microarray analysis of blood cells from P. chabaudi-infected mice, Kim et al (18) reported a rapid production of IFN-␥ and activation of IFN-␥-mediated signaling pathways as early as 8 h after infection; however, NK cells did not express IFN-␥ or exhibit IFN-␥-mediated pathways in their analysis. At this time, NK cells are replicating and migrating from the spleen to the blood.…”
mentioning
confidence: 99%
“…39 Additionally, a protective role for various components of the innate immune response, particularly dendritic cells and NK cells, has been established. 41,42 Many of the key host immune factors have been characterized using mouse models. For example, CD4 þ T-cell depleted mice show high levels of peak parasitemia and are subsequently unable to clear parasites during the chronic phase, 39 whereas IFNg knockout mice experience uncontrolled parasite replication and all mice succumb to hyper-parasitemia and anemia.…”
Section: Discussionmentioning
confidence: 99%